2014
DOI: 10.1177/0306624x13516732
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Offender Recidivism Among a Population-Based Prison Sample

Abstract: The present study examines recidivism rates in sexual offenders using officially registered reconvictions in a representative data set of N = 1,115 male sexual offenders from Austria. In general, results indicate that most sexual offenders do not reoffend sexually after release from prison. More detailed, within the first 5 years after release, the sexual recidivism rate was 6% for the total sample, 4% for the rapist subgroup, and 8% for the child molester subgroup. The findings confirmed previous studies abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…Thus, the reduction in one motivational force (e.g., sexual hormones) could still leave sexual delinquent behaviour motivated by a range of other forces. Even if these considerations are far beyond the scope of the present study, it becomes clear that also previous studies found similar result patterns when using representative prison samples of sexual offenders (Rettenberger, Briken, Turner, & Eher, 2015;Thornton, 2006).…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the reduction in one motivational force (e.g., sexual hormones) could still leave sexual delinquent behaviour motivated by a range of other forces. Even if these considerations are far beyond the scope of the present study, it becomes clear that also previous studies found similar result patterns when using representative prison samples of sexual offenders (Rettenberger, Briken, Turner, & Eher, 2015;Thornton, 2006).…”
Section: Discussionsupporting
confidence: 70%
“…By way of exception, the group of over-50s who scored in the highest risk band exhibited a high rate of sexual recidivism (40.0%); however, it is important to note this group was small in numbers (n = 20, eight of whom were reconvicted). Other studies (e.g., Rettenberger, Briken, Turner, & Eher, 2015;Thornton, 2006) have reported more complex relationships between age and sexual recidivism as opposed to a simple linear decline, though nonetheless found substantially reduced rates after the age of 60.…”
Section: Age and Desistence From Sexual Violence Across The Lifespanmentioning
confidence: 75%
“…This enabled us to characterize two subgroups of MDSOs, one with psychotic disorders and one without. Most studies on general sex offenders do not include offenders with psychotic disorders, or do not specifically discuss this subgroup (3,10,24,25). Even in studies on MDSOs, data on offenders with psychotic disorders are rarely consistent (12,26‐31).…”
Section: Discussionmentioning
confidence: 99%